2018
DOI: 10.1021/acs.orglett.8b01249
|View full text |Cite
|
Sign up to set email alerts
|

Radical Chlorodifluoromethylation: Providing a Motif for (Hetero)arene Diversification

Abstract: A method for the radical chlorodifluoromethylation of (hetero)arenes using chlorodifluoroacetic anhydride is reported. This operationally simple protocol proceeds under mild photochemical conditions with high functional group compatibility and complements the large body of literature for the trifluoromethylation of (hetero)arenes. Introduction of the chlorodifluoromethyl motif enables rapid diversification to a wide array of aromatic scaffolds. This work showcases the chlorodifluoromethyl group as an attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 65 publications
1
44
0
Order By: Relevance
“…Through a collaboration with Eli Lilly this scale was increased to 1.2 kg in a continuous flow system (50 % yield) . The methodology was later on expanded to radical perfluoroalkylation and chloro‐difluoromethylation of (hetero)arenes …”
Section: C–c Bond: Sp2‐sp3 Disconnectionmentioning
confidence: 99%
“…Through a collaboration with Eli Lilly this scale was increased to 1.2 kg in a continuous flow system (50 % yield) . The methodology was later on expanded to radical perfluoroalkylation and chloro‐difluoromethylation of (hetero)arenes …”
Section: C–c Bond: Sp2‐sp3 Disconnectionmentioning
confidence: 99%
“…McAtee, Stephenson, and colleagues [35] have informed the chloro-difluoromethylation of (hetero)arenes. While the difluoromethyl radical CF 2 H exhibits nucleophilic behavior, the chlorodifluoromethyl CF 2 Cl radical may be characterized as an electrophilic radical.…”
Section: (Het) -H Difluoromethylation Of (Hetero)aromatic Compoundsmentioning
confidence: 99%
“…Therefore, the CF 2 Cl radical can be considered as an attractive surrogate to the difluoromethyl radical and a means to efficiently prepare electron-rich difluoromethylated (hetero)arenes and other high-value, fluorinated heterocycles. The authors in [35] employed commercially available chlorodifluoroacetic anhydride as a source of CF 2 Cl radicals and found that with benzene as the substrate, a combination of pyridine-N-oxide, chlorodifluoroacetic anhydride, photocatalyst Ru(bpy) 2 Scheme 1. Selected examples of chlorodifluoromethylation of (hetero)arenes.…”
Section: (Het) -H Difluoromethylation Of (Hetero)aromatic Compoundsmentioning
confidence: 99%
“…Stephenson's group achieved the radical chloro‐difluoromethylation of arenes and heteroarenes ( 190 ) by in situ formation of a redox‐active complex resulting from the combination of heterocyclic N ‐oxides (pyridine N ‐oxide and 4‐phenylpyridine N ‐oxide) with the commercially available chlorodifluoroacetic anhydride [(ClCF 2 CO) 2 O, CAS number: 2834‐23‐3], in the presence of [Ru(bpy) 3 ]Cl 2. Electron‐rich heteroarenes and other pharmaceutically valuable agents with diverse functional groups were competent substrates for the desired organic transformation under both batch and flow conditions ( 191 , Scheme : 19 examples, 25–84% yields). Interestingly, the chlorodifluoromethyl group‐containing compounds ( 191 ) can be used as synthetic percursors to access electron‐rich difluoromethylated arenes and heteroarenes.…”
Section: General Introductionmentioning
confidence: 99%